Mapping spheres of literacy: the home and school environment in the invention of the reader - Silva, Thaise da (FCL-UNESP Laboratório Editorial, 2018)
This article aims to discuss the reading social practices of students in the domestic environment and their interactions with the school sphere. From the perspective of literacy studies, itself based on cultural studies, it analyzes the spaces and the bearers of texts that usually populate them, and also discusses the “discourse on reading renewal” which colors the way respondents relate to the subject. The methodological tools used for this research are textual and discursive analysis. The materials collected during the investigation were questionnaires presented to students and their families with enquiries regarding their reading habits and the materials used, primarily in their homes. The results obtained show that the vast majority of the families and children targeted by the study perceive reading as a fundamental tool in forming future citizens, and that many also brought with them the principles that guide the “discourse on reading renewal”.